Climate resilience initiatives at IIVR, Varanasi - Singh, Major; Rai, N.; Kumar, Rajesh; Tiwari, S. K.; Bahadur, Anant; Rai, A. B. (Indian Horticulture, 2019)
A significant change in climate on a global scale will impact vegetable cultivation and agriculture as a whole; consequently affecting the world’s food supply. Climate change will influence the severity of environmental stress imposed on vegetable crops and moreover, increasing temperatures, reduced irrigation water availability, and flooding will be major limiting factors in sustaining and increasing vegetable productivity. Screened genotype has been used to develop new variety for different stress. The tomato genotypes CLN- 1621, CLN-2026, EC-620421, and EC-620419 are better under high temperature stress, whereas EC-625659 is high yielding in low moisture deficit condition.